Regression equations to predict 6-minue walk distance in Chinese adults aged 55-85 years - Ngai, S.; Jones, A.; Jenkins, Susan (Elsevier, 2014)
The 6-minute walk distance (6MWD) is used as a measure of functional exercise capacity in clinical populations and research. Reference equations to predict 6MWD in different populations have been established, however, available equations for Chinese population are scarce. This study aimed to develop regression equations to predict the 6MWD for a Hong Kong Chinese population. Fifty-three healthy individuals (25 men, 28 women; mean age = 69.3 ± 6.5 years) participated in this cross-sectional study. Each participant performed two 6-minute walk tests (6MWTs) in accordance with a standard protocol. Heart rate (HR) was continuously monitored throughout the 6MWTs and the maximum HR was recorded. Measurements from the 6MWT that resulted in the highest 6MWD were used for regression analysis. The mean 6MWD was 563 ± 62 m and was significantly correlated with age (r = −0.62), height (r = 0.39), and percentage of predicted maximal HR (%predHRmax; r = 0.50). A regression equation derived from the data showed that age, sex, and %predHRmax were independent contributors and together explained 65% of the variance in 6MWD. When HR was excluded, the equation explained 52% of the variance. Application of these equations to a Chinese population living in different parts of China warrants further investigation.